Diversity of group A rotavirus on a UK pig farm - Chandler-Bostock, Rebecca; Hancox, L.R.; Payne, Helen; Iturriza-Gomara, Miren; Daly, Janet M.; Mellits, K.H. (Elsevier, 2015)
Group A rotaviruses (GARV) are a significant cause of enteritis in young pigs. The aim of this study was to extend our understanding of the molecular epidemiology of porcine GARV in the UK by investigating the genetic diversity of GARV on a conventional farrow-to-finish farm. Faecal samples were obtained from six batches of pigs in 2009 and 8 batches in 2010, when the pigs were 2, 3 (time point omitted in 2009), 4, 5, 6 and 8 weeks of age. Presence of rotavirus was detected by reverse transcriptase-polymerase chain reaction (RT-PCR) in 89% and 80% of samples from 2009 and 2010, respectively. A combination of multiplex PCRs and sequencing identified four VP7 genotypes (G2, G3, G4 and G5) and three VP4 genotypes (P[6], P[7] and P[32]) present in almost every combination over the 2 years. The predominant genotype combination was G5P[32] in 2009 and G4P[32] in 2010. Conservation among the P[32] sequences between 2009 and 2010 suggests that reassortment may have led to the different genotype combinations. There were significant changes in the predominant VP7 genotype prior to weaning at 4 weeks, and post weaning when pigs were moved to a different building. Phylogenetic analysis indicated that introduction of new viruses onto the farm was limited. Taken together, these findings suggest that genetically diverse GARV strains persist within the farm environment.